The war puzzle - Vasquez, John A. (Cambridge studies in international relations, 1993)
This book constructs a new scientific explanation of the onset and expansion of war and the conditions of peace. The author describes systematically those factors common to wars between equal states to see if there is a pattern that suggests why war occurs, and how it might be avoided or mitigated, delineating the typical path by which relatively equal states have become embroiled in wars with one another in the modern global system. Emphasis is placed on the issues that give rise to war and how the practices of power politics lead to a series of steps that produce war rather than peace. The book differs from others in that it employs the large number of empirical findings generated in the last twenty-five years as the basis of its theorizing, and integrates these research findings so as to advance dramatically the scientific knowledge of war and peace.